Utilization of Beliefs and Food Taboos in The ’Horse-Man’ Myth as BIPA Learning Content in East-Timor - Elisabeth Merniana Bera; Nuny Sulistiany Idris; Suci Sundusiah (Indonesian Language Education and Literature, 2025)
This research analyzes the "Horse-Human" myth from Uma Lisan Bihahi, Timor-Leste as a potential study for Indonesian Language for Foreign Speakers (BIPA) instructional materials through Todorov's structural narrative approach, analyzed with Content-Based Instruction theory and Actor-Network Theory. Employing qualitative methods with an exploratory case study design, this research involved six informants from three different Uma Lisan in Timor-Leste through in-depth interviews and participant observation. Structural analysis revealed 36 narrative functions that form hierarchical transformation patterns from initial famine situations to human-to-horse metamorphosis, creating a food taboo system that functions as a mechanism for social control and cultural identity preservation. The findings demonstrate that this myth possesses a complex narrative structure in which each element can be identified as having potential for BIPA learning content through the exploration of four language skills (listening, speaking, reading, writing) with authentic local cultural content. The belief system and food taboos within the myth function as vehicles for transmitting local wisdom values encompassing respect for nature, family sacrifice, and animal sacredness in traditional Timorese cosmology. The potential utilization of myths as BIPA learning content has the potential to enhance learners' linguistic competence as well as intercultural communicative competence through a deep understanding of Timorese worldviews. This research contributes methodologically through narrative structural analysis that supports the exploration of cultural content as BIPA learning materials based on local wisdom that can be adapted for utilizing other oral traditions, while simultaneously supporting intangible cultural heritage preservation efforts through the exploration of contextual and culturally meaningful language education.Pemanfaatan Kepercayaan dan Tabu Pangan pada Mite “Manusia Kuda” sebagai Konten Belajar BIPA di Timor LestePenelitian ini menganalisis mite "Manusia Kuda" dari Uma Lisan Bihahi, Timor-Leste sebagai kajian potensi bahan ajar Bahasa Indonesia bagi Penutur Asing (BIPA) melalui pendekatan struktural naratif Todorov yang dianalisis dengan teori Content-Based Instruction dan Actor-Network Theory. Menggunakan metode kualitatif dengan desain studi kasus eksploratif, penelitian ini melibatkan enam informan dari tiga Uma Lisan berbeda di Timor-Leste melalui wawancara mendalam dan observasi partisipan. Analisis struktural mengungkapkan 36 fungsi naratif yang membentuk pola transformasi berjenjang dari situasi awal kelaparan hingga metamorfosis manusia menjadi kuda, menciptakan sistem tabu pangan yang berfungsi sebagai mekanisme kontrol sosial dan preservasi identitas budaya. Temuan menunjukkan bahwa mite ini memiliki struktur naratif kompleks yang dapat diidentifikasi pada setiap elemen yang potensial untuk konten pembelajaran BIPA melalui eksplorasi empat keterampilan berbahasa (menyimak, berbicara, membaca, menulis) dengan konten budaya lokal yang autentik. Sistem kepercayaan dan tabu pangan dalam mite berfungsi sebagai wahana transmisi nilai-nilai kearifan lokal yang mencakup penghormatan terhadap alam, pengorbanan keluarga, dan kesakralan hewan dalam kosmologi tradisional Timor-Leste. Potensi pemanfaatan mite sebagai konten pembelajaran BIPA berpotensi meningkatkan kompetensi linguistik pembelajaran tetapi juga kompetensi komunikatif interkultural melalui pemahaman mendalam tentang pandangan dunia masyarakat Timor-Leste. Penelitian ini berkontribusi metodologis berupa analisis struktur naratif yang mendukung eksplorasi konten budaya sebagai bahan pembelajaran BIPA berbasis kearifan lokal yang dapat diadaptasi untuk pemanfaatan tradisi lisan lainnya, sekaligus mendukung upaya pelestarian warisan budaya takbenda melalui eksplorasi pendidikan bahasa yang kontekstual dan bermakna budaya.